Mysteries of the sea : how divers explore the ocean depths - Morrison, Marianne (Washington, D.C. : National Geographic, 2006)
Introduces underwater exploration, discussing the four zones of the ocean, divers and their equipment, and other related topics.
Includes bibliographical references (p. 39) and index.
3.8
K-3
K-3
Keywords: Underwater exploration -- Juvenile literature; Deep diving -- Juvenile literature; Underwater exploration; Deep diving; Ocean; Underwater exploration; Deep diving; Ocean